Reconstruction of Restrictions on the President's Power in Determining the Posture of Ministries in the Indonesian Government System - Saifulloh, Putra Perdana Ahmad; Yuliandri, Yuliandri; Simabura, Charles; Fahmi, Khairul; Nur, Asrul Ibrahim (Universitas Negeri Gorontalo, 2025)
This research is a critique of the 2024 State Ministry Law which gives the President the freedom to form Ministries according to his needs.. Based on this law, the President, Prabowo Subianto, formed a Cabinet consisting of 48 Ministries. For this reason, it is urgent to immediately enact a Presidential Agency Law to limit the President's power in determining the posture of ministries so that their functions do not overlap, do not reflect cabinet affairs, and prevent corruption. Through the Presidential Agency Law, it is hoped that the President will not use Ministerial positions as political barter and